2015
DOI: 10.1016/j.tics.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing and reconstructing theory of mind

Abstract: Usage of the term Theory of Mind (ToM) has exploded across fields ranging from developmental psychology to social neuroscience and psychiatry research. Yet its meaning is often vague and inconsistent, its biological bases are a subject of debate, and the methods used to study it are highly heterogeneous. Most critically, its original definition does not permit easy downward translation to more basic processes such as those studied by behavioral neuroscience, leaving the interpretation of neuroimaging results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
303
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 405 publications
(322 citation statements)
references
References 73 publications
11
303
1
7
Order By: Relevance
“…It remains possible that, even in adulthood, the amygdala plays a key role in the bottom-up control of cortical networks for ToM use, but this role may be revealed only on tasks that are relatively implicit in their cognitive demands, such as nonverbal tasks. This suggestion highlights the more general theme that ToM is quite heterogeneous in its behavioral expression, operational definition, and neural correlates (28,35,36). A more comprehensive investigation, such as the one in the present paper but over a larger battery of ToM tasks, could help parse that heterogeneity into types that do not depend on the amygdala and types that may.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It remains possible that, even in adulthood, the amygdala plays a key role in the bottom-up control of cortical networks for ToM use, but this role may be revealed only on tasks that are relatively implicit in their cognitive demands, such as nonverbal tasks. This suggestion highlights the more general theme that ToM is quite heterogeneous in its behavioral expression, operational definition, and neural correlates (28,35,36). A more comprehensive investigation, such as the one in the present paper but over a larger battery of ToM tasks, could help parse that heterogeneity into types that do not depend on the amygdala and types that may.…”
Section: Discussionmentioning
confidence: 56%
“…At the outset, we clarify that the False-Belief Localizer does not exhaustively represent the range and complexity of the human capacity to reason about mental states (35). In fact, many different behavioral tasks have been used to manipulate mentalstate reasoning in previous neuroimaging studies (23,26), and recent evidence has demonstrated convincingly that these various tasks are not interchangeable manipulations of a single ToM capacity but rather modulate dissociable cortical networks (28,36).…”
mentioning
confidence: 83%
“…We prefer the term psychological reasoning for two reasons (see also Schaafsma et al 2015). First, this term underscores the deep similarities between infants' psychological reasoning and their reasoning in other core domains of causal reasoning, such as physical and sociomoral reasoning (e.g., Baillargeon et al 2013Baillargeon et al , 2015.…”
Section: Implicit and Explicit Psychological Reasoningmentioning
confidence: 99%
“…However, a single perspective cannot tackle such a multilayered phenomenon as human behavior, whereas it may be useful to Bdecompose^ (Schaafsma et al, 2015) complexity starting from more basic neurobiological, neurophysiological, and neurocognitive components. Worth noting is that the DSM-5 strategy, driven by recent advances in genetics and neuroscience-in contrast to the descriptive and phenomenological approach of the DSM IV-is consistent with such a view (Regier, Kuhl, & Kupfer, 2013).…”
Section: Motor Cognition In Asd: Motor Anomalies Impacting On Social mentioning
confidence: 99%
“…However, the putative neural correlates of the so-called Bmentalizing system^remain controversial in the literature (Fishman, Keown, Lincoln, Pineda, & Muller, 2014;Mainieri, Heim, Straube, Binkofski, & Kircher, 2013;Mitchell, 2008; for a meta-analysis, see Schurz, Radua, Aichhorn, Richlan, & Perner, 2014). Plausibly, these controversies may be due to the ambiguities of defining in operational terms the notion of ToM, and to the misleading idea that ToM is a unitary process (Bloom & German, 2000;Schaafsma, Pfaff, Spunt, & Adolphs, 2015). To overcome the idea that social cognition involves Bsocial metacognitionê xclusively (Gallese, 2007), a new approach has been proposed: a multilevel action understanding model that claims that we can understand others' actions through different, non-mutually exclusive, and non-competitive ways (Casartelli & Molteni, 2014;de Waal & Ferrari, 2010).…”
mentioning
confidence: 99%